Paylater And Generation Z: What Drives Paylater Use? - Ni Made Dwi Damayanti; Gusi Putu Lestara Permana (Penerbit Goodwood, 2025)
Purpose: This study investigates the impact of financial literacy and convenient payment systems on the use of PayLater services among Generation Z in Denpasar. Methodology/approach: The research involved 100 Gen Z respondents in Denpasar who had experience using PayLater. Data were collected through a Likert-scale questionnaire and analyzed quantitatively using SPSS, including validity and reliability testing, classical assumption tests, multiple linear regression, and hypothesis testing (t-test and F-test). Results/findings: The findings reveal that financial literacy has a negative yet significant effect on PayLater usage, while convenient payment systems exert a positive and significant influence. Together, both variables significantly affect decisions to adopt PayLater services among Generation Z in Denpasar. Limitations: This study focuses only on Gen Z in Denpasar and examines two independent variables, namely financial literacy and convenient payment systems. Other factors, such as lifestyle, promotions, or self-control, were not explored. Conclusion: Financial literacy negatively affects PayLater adoption, whereas convenient payment systems have a positive influence. Combined, these factors explain PayLater usage behavior in line with the theory of planned behavior. Although PayLater offers convenience, financial literacy remains essential to mitigate risks. Contribution: The study contributes by expanding literature on financial literacy and consumer behavior in fintech, providing insights for providers to balance ease with financial education, and raising awareness among young users to apply PayLater responsibly.